Fertility preservation in reproductive-age women facing gonadotoxic treatments - Roberts, J. (Curr Oncol, 2015)
BACKGROUND: Advancements in the treatments for cancer and autoimmune and other hematologic conditions continue to improve survival and cure rates. Despite those changes, various gonadotoxic agents and other treatments can still compromise the future fertility of many women. Progress in medical and surgical reproductive technologies has helped to offset the reproductive consequences of the use of gonadotoxic therapies, and allows for future fertility and normal pregnancy. METHODS: A review of the literature was performed to outline the pathophysiology of gonadotoxicity from various treatments. The success of fertility preservation, fertility sparing, and cryopreservation options are reviewed. Barriers and facilitators to referral and oncofertility treatment in Canada are also outlined. RESULTS: According to the quality of the evidence, recommendations are made for fertility assessment, patient referral, cryopreservation, and other assisted reproductive technologies. CONCLUSIONS: To ensure ongoing fertility in women undergoing gonadotoxic treatments, assisted reproductive technologies can be combined with a multidisciplinary approach to patient assessment and referral.